2003
DOI: 10.1177/1077801202239004
|View full text |Cite
|
Sign up to set email alerts
|

The Intimate Partner Violence Strategies Index

Abstract: Although research has documented the myriad ways that victims of IPV struggle to keep themselves safe, little research has gone the next step to investigate patterns in women's use of strategies, the factors that influence choice of strategies, or which strategies are most effective. One obstacle to conducting such research is the absence of an instrument to measure the nature and extent of battered women's strategic responses to violence across specific domains of strategies. This article describes the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
164
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(176 citation statements)
references
References 10 publications
12
164
0
Order By: Relevance
“…Additionally, most studies assessing the helpfulness of a strategy did so using a likert scale and not a dichotomous item. Because these studies reported on mean scores for those scales, comparisons were incompatible (Parker & Gielen, 2014;Goodman et al, 2003). No information could be found from existing literature about whether or not other participants would recommend safety planning or certain strategies for friends.…”
Section: Acceptabilitymentioning
confidence: 88%
See 4 more Smart Citations
“…Additionally, most studies assessing the helpfulness of a strategy did so using a likert scale and not a dichotomous item. Because these studies reported on mean scores for those scales, comparisons were incompatible (Parker & Gielen, 2014;Goodman et al, 2003). No information could be found from existing literature about whether or not other participants would recommend safety planning or certain strategies for friends.…”
Section: Acceptabilitymentioning
confidence: 88%
“…Other studies found 69.1% talked with family, 74.5% talked with friends (Cooker as cited in Parker & Gielen, 2014) or 64% talked with a friend, and 49% talked with a family member (Glass et al, 2010). As mentioned above, this strategy has been shown to be particularly helpful (Goodman et al, 2003).…”
Section: Feasibility: Domain 3 Usefulness Of Safety Plan and Strategiesmentioning
confidence: 98%
See 3 more Smart Citations